Evaluation of decubitus ulcers in palliative care center - Gürlek, Feridun; Taşdemir, Eyyüp; Erol, Ali (International Journal of Research in Medical Sciences, 2024)
Background: Decubitus is ulcerated wounds occurring in the body regions that are exposed to prolonged pressure. Predisposition to decubitus is not fully understood. In this study, we aimed to investigate this opinion in the light of the literature. Methods: Retrospective screening of patients in palliative care center between May 2016 and September 2017 were made with medical records of University of Health Sciences, Bursa Yuksek Ihtisas Training and Research Hospital. A total of 113 patients 43.4% (n=49) female; mean age:67.03±20.42 years hospitalized in the palliative care were included in the study. Results: Decubitus was found in 64% (n=16) of 25 patients admitted from house, 69.6% (n=16) of 23 patients referred from the inpatient service, and 66.2% (n=43) of 65 patients referred from the intensive care unit. Conclusions: No statistically significant difference were present between incidences of decubitus according to the status of admission. Decubitus ulcers may develop due to patient and care factors independent from time and location. This study supports this opinion by comparing the incidences between ICU, houses, and hospitals, in the light of the literature.